Next-generation sequencing of advanced prostate cancer treated with androgen-deprivation therapy. - Rajan, P; Sudbery, I; Villasevil, M; Mui, E; Fleming, J; Davis, M; Ahmad, I; Edwards, J; Sansom, O; Sims, D; Ponting, C; Heger, A; et al. (2014)
Androgen-deprivation therapy (ADT) is standard treatment for locally advanced or metastatic prostate cancer (PCa). Many patients develop castration resistance (castration-resistant PCa [CRPC]) after approximately 2-3 yr, with a poor prognosis. The molecular mechanisms underlying CRPC progression are unclear.To undertake quantitative tumour transcriptome profiling prior to and following ADT to identify functionally important androgen-regulated pathways or genes that may be reactivated in CRPC.RNA sequencing (RNA-seq) was performed on tumour-rich, targeted prostatic biopsies from seven patients with locally advanced or metastatic PCa before and approximately 22 wk after ADT initiation. Differentially regulated genes were identified in treatment pairs and further investigated by quantitative reverse transcription-polymerase chain reaction (qRT-PCR) on cell lines and immunohistochemistry on a separate CRPC patient cohort. Functional assays were used to determine the effect of pathway modulation on cell phenotypes.We searched for gene expression changes affecting key cell signalling pathways that may be targeted as proof of principle in a CRPC in vitro cell line model.We identified ADT-regulated signalling pathways, including the Wnt/β-catenin signalling pathway, and observed overexpression of β-catenin in a subset of CRPC by immunohistochemistry. We validated 6 of 12 (50%) pathway members by qRT-PCR on LNCaP/LNCaP-AI cell RNAs, of which 4 (67%) demonstrated expression changes consistent with RNA-seq data. We show that the tankyrase inhibitor XAV939 (which promotes β-catenin degradation) reduced androgen-independent LNCaP-AI cell line growth compared with androgen-responsive LNCaP cells via an accumulation of cell proportions in the G0/G1 phase and reduction in the S and G2/M phases. Our biopsy protocol did not account for tumour heterogeneity, and pathway inhibition was limited to pharmacologic approaches.RNA-seq of paired PCa samples revealed ADT-regulated signalling pathways. Proof-of-principle inhibition of the Wnt/β-catenin signalling pathway specifically delays androgen-independent PCa cell cycle progression and proliferation and warrants further investigation as a potential target for therapy for CRPC.